Metadata - Hopkinson, Alan (Infotheca - Journal for Digital Humanities; Vol 5 No Special is (2004): Infotheca - Journal of Informatics and Librarianship, 2024)
Metadata is a large topic and in this paper I will discuss what librarians mean by metadata and the use of metadata in the book trade. I will not be talking very much about metadata in museums and archives though I will touch on that topic.